Evaluation of the Anticancer Potential of Crude, Irradiated Cerastes cerastes Snake Venom and Propolis Ethanolic Extract & Related Biological Alterations - Mostafa I. Abdelglil; Sanaa O. Abdallah; Mohamed A. El-Desouky; Mohammad Y. Alfaifi; Serag Eldin I. Elbehairi; Aly F. Mohamed (Molecules, 2021)
We aimed to evaluate the anticancer potential of crude venom (CV), γ irradiated Certastes cerastes venom (IRRV), and propolis ethanolic extract (PEE). IRRV showed a higher toxicity than CV, while CV-PEE showed higher toxicity than IRRV and CV against lung [A549] and prostate [PC3] cancer cells. Toxicity to [A549] and [PC3] cells was concentration and cell type dependent. In comparison to controls, apoptotic genes showed a significant upregulation of P53 and Casp-3 and a downregulation of Bcl-2. Also, induced elevated DNA accumulation in the [S] phase post PC3 cell treatment with IRRV and CV, as well as a significant DNA accumulation at G2/M phase after IRRV treatment of A549 cells. In contrast, PC3 cells showed a negligible cellular DNA accumulation after PEE treatment. Glutathione reductase [GR] was reduced in case of PC3 and A549 cell treated with IRRV, CV, and PEE compared with its values in untreated cell control. The Malondialdehyde [MDA] values in both cells recorded a significant elevation post IRRV treatment compared to the rest of the treatment regimen and untreated cell control. Similarly, IRRV and CV-PEE mix showed obviously higher reactive oxygen species [ROS] values than PC3 and A549 cell treatments with CV and PEE.